2018
DOI: 10.1136/bmjopen-2017-019224
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centred attitudes among medical students in Mali, West Africa: a cross-sectional study

Abstract: Background/objectivePatient-centred attitudes have been shown to decline during medical training in high-income countries, yet little is known about attitudes among West African medical students. We sought to measure student attitudes towards patient-centredness and examine validity of the 18-item Patient–Practitioner Orientation Scale (PPOS) in this context.Participants/setting430 medical students in years 1, 3, 5 and 6 of a 6-year medical training programme in Bamako, Mali.DesignWe conducted a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 36 publications
5
34
1
4
Order By: Relevance
“…In general, Chinese medical students tended toward patient-centred attitudes, as indicated by a mean CR-PPOS score of 3.63 (scores higher than 3.5 indicate patient-centred attitudes), which is higher than Malian (3.38) and Pakistani (3.40) medical students but lower than American (4.57) and Brazilian (4.66) medical students (Hurley et al, 2018; Ribeiro, Krupat & Amaral, 2007; Haidet et al, 2002; Ahmad et al, 2015). The Chinese medical students’ ‘Sharing’ subscales (2.88) were generally lower than Malian (3.04), Pakistani (3.18), and Brazilian (4.10) medical student scores.…”
Section: Discussionmentioning
confidence: 94%
“…In general, Chinese medical students tended toward patient-centred attitudes, as indicated by a mean CR-PPOS score of 3.63 (scores higher than 3.5 indicate patient-centred attitudes), which is higher than Malian (3.38) and Pakistani (3.40) medical students but lower than American (4.57) and Brazilian (4.66) medical students (Hurley et al, 2018; Ribeiro, Krupat & Amaral, 2007; Haidet et al, 2002; Ahmad et al, 2015). The Chinese medical students’ ‘Sharing’ subscales (2.88) were generally lower than Malian (3.04), Pakistani (3.18), and Brazilian (4.10) medical student scores.…”
Section: Discussionmentioning
confidence: 94%
“…(Haidet et al, 2002;Ribeiro et al, 2007;Lee et al, 2008b) In general, Chinese medical students tended toward patient-centred attitudes, as indicated by a mean CR-PPOS score of 3.63 (scores higher than 3.5 indicate patient-centred attitudes), which is higher than Malian (3.38) and Pakistani (3.40) medical students but lower than American (4.57) and Brazilian (4.66) medical students. (Hurley et al, 2018;Ribeiro et al, 2007;Haidet et al, 2002;Ahmad et al, 2015) The Chinese medical students' 'Sharing' subscales (2.88) were generally lower than Malian (3.04), Pakistani (3.18), and Brazilian (4.10) medical student scores. However, the Chinese medical students' 'Caring' subscales (4.53) were generally lower than Brazilian students (5.20) but higher than Pakistani (3.63) and Malian (3.68) students.…”
Section: Ppos Scores For Different Major Categories and Gendermentioning
confidence: 98%
“…It is a similar to Africa's cultures that have similarly seen higher caring scores as compared to sharing. (Lee et al, 2008b;Searight & Gafford, 2005;Tai & Tsai, 2003;Hurley et al, 2018) In China, Ting et al found that patients were more likely to rely on doctors to control consultations, decision-making, and information distribution; also, Ting et al established that patients do not think that they have the knowledge or ability to handle medical issues. (Ting et al, 2016; The higher 'Caring' subscales might be due to medical students hoping that doctor-patient relationships can be based on mutual understanding…”
Section: Ppos Scores For Different Major Categories and Gendermentioning
confidence: 99%
“…A curriculum that emphasizes on biological aspects of diseases has no efficiency in institutionalizing of such attitude. The intensity of the workload and responsibilities of medical students, which can lead to burn out, is another reason (7). However, the evidence on this regard is contradictory so that some other similar studies indicate an increase or no significant change in patient-centeredness attitude during the course of study (8,9).…”
Section: Introductionmentioning
confidence: 99%